White Sago Beta from Maluku (Digging From the Exact Philosophy of a Kind of Sago Tree) - Marcus F. Pessireron (Program Pascasarjana Universitas Negeri Makassar, 2023)
This study aims to obtain in-depth information regarding the public's view of beta white sago from Maluku; digging from the exact philosophy of macang sago tree. This type of research is qualitative. In collecting data, the researcher collected in-depth and comprehensive information to obtain an overview of the phenomena that occur in the lives of local people in Maluku about the white sago beta perisis macang sago tree. The data was obtained through two sources, namely; documentation and informants. Data collection techniques were carried out through in-depth interviews. The data is then analyzed using interactive analysis techniques intended to see the process, the application of local community behavior with the philosophy of Perisis of the Sago Tree Kind. The results of this study show the views and judgments of the community that white sago humans are just like the macang sago palms that are dirty on the outside but clean on the inside. The philosophy of the sago tree is very populist, that sago as the staple food of the Ambonese can be economically managed and produced so that it can improve the economic welfare of the local community.